Cerium-doped bismuth tungstate loaded osmium photoelectrocatalytic material and preparation method thereof

CN118022731BActive Publication Date: 2026-10-09SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410165312.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-05
Publication Date
2026-10-09
Estimated Expiration
2044-02-05

AI Technical Summary

Technical Problem

然而未经改性的钨酸铋仍存在光生载流子易复合和可见光利用率低等问题使其未达到理论应用价值,因此需要对其改性来提升光电催化性能

Benefits of technology

[0020] This invention discloses a method for preparing osmium photocatalyst material supported on cerium-doped bismuth tungstate. The method involves introducing and regulating crystal defects by doping Bi₂WO₆ with the rare earth element Ce (Ce partially replaces Bi), thereby generating oxygen vacancies to enhance the visible light response of the semiconductor. Appropriate amounts of oxygen vacancies not only facilitate carrier separation but also extend the semiconductor's photoresponse into the visible light region. The osmium is uniformly dispersed with osmium powder in deionized water, and the deionized water is evaporated using a water bath. This allows osmium to be loaded onto the cerium-doped bismuth tungstate. Finally, after drying and grinding, the cerium-doped bismuth tungstate-supported osmium photocatalyst material is obtained. This invention uses a water bath heating method to load metal Os. Because Os has a smaller work function than bismuth tungstate, loading it onto cerium-doped bismuth tungstate creates an ohmic contact. The band bending caused by the ohmic contact prevents charge carrier migration from Os to the cerium-doped bismuth tungstate. Simultaneously, there is no barrier for electrons to enter the metal from the semiconductor, which promotes the migration of photogenerated charge carriers. Incorporating the effects of the built-in electric field and ohmic contact, the transfer rate of photogenerated electrons from Os to cerium-doped bismuth tungstate is extremely fast, approaching zero resistance migration. This directly and effectively improves carrier separation efficiency, thereby achieving higher photocatalytic performance. This invention designs an osmium-supported cerium-doped bismuth tungstate photocatalytic material based on the principles of greenness, simplicity, and efficiency. It is easy to operate, has a relatively simple process, and yields products with uniform particle size.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118022731B_ABST
    Figure CN118022731B_ABST
Patent Text Reader

Abstract

The application provides a cerium-doped bismuth tungstate loaded osmium photoelectrocatalytic material and a preparation method thereof. The method comprises the following steps: dissolving bismuth nitrate, sodium tungstate and cerium nitrate in deionized water, wherein the molar ratio of bismuth nitrate and cerium nitrate is 5:1, to obtain a mixed solution; adjusting the pH of the mixed solution to 7-8 to obtain a precursor solution; and performing heat preservation treatment on the precursor solution at 180-210 DEG C to obtain a reaction solution; and after washing and drying the product in the reaction solution, grinding is performed to obtain cerium-doped bismuth tungstate. The cerium-doped bismuth tungstate and osmium powder are uniformly dispersed in deionized water at a mass ratio of 699:(28-143), and then the deionized water is evaporated by means of water bath, so that the osmium is loaded on the cerium-doped bismuth tungstate to obtain a composite. After drying and grinding the composite, a cerium-doped bismuth tungstate loaded osmium photoelectrocatalytic material is obtained. The loading of osmium effectively promotes the interface charge transfer and provides more active sites, so that the photoelectrochemical performance is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photoelectrocatalytic material preparation, specifically a cerium-doped bismuth tungstate supported osmium photoelectrocatalytic material and its preparation method. Background Technology

[0002] With the rapid development of science and technology, the demand for coal, oil, natural gas, and other mineral energy sources is constantly increasing, and humanity remains dependent on these minerals and energy sources. The problem of energy supply shortages is becoming increasingly serious, making the development and utilization of new energy technologies an urgent matter for human development. Scientists have begun to focus on new renewable energy sources such as solar energy, bioenergy, geothermal energy, and hydrogen energy. Among these, hydrogen energy, due to its advantages of high energy density, environmental friendliness, and no secondary pollution, is widely used in various new energy fields. Photoelectrochemical water splitting technology is a feasible way to produce hydrogen from solar energy and realize the utilization of solar energy, and it is also one of the most promising strategies to solve the energy crisis. Selecting and preparing suitable photoelectrode materials is crucial for achieving efficient photoelectrochemical water splitting for hydrogen production.

[0003] The core of photoelectrocatalysis technology lies in the development of highly efficient photocatalysts. Among numerous photocatalytic material systems, bismuth tungstate (Bi₂WO₆), as the simplest semiconductor material in the Aurivillius family, is a typical n-type semiconductor with a band gap of approximately 2.76 eV. The valence band of Bi₂WO₆ is formed by O 2p and Bi 6p orbitals with the assistance of Bi 6s hybrid orbitals, while its conduction band is formed by W 5d orbitals with the assistance of Bi 6p orbitals. The hybridization of Bi 6s and O 2p leads to a large dispersion of holes in the valence band, thereby accelerating hole migration and enhancing its oxidation capacity. Bi₂WO₆ is composed of (Bi₂O₂). 2+ Layers and (WO4) 2- The perovskite sheet structure, formed by alternating stacked layers, possesses a unique electronic structure and excellent photoelectric properties, making it a potential candidate for photoelectrocatalysis. However, unmodified bismuth tungstate suffers from problems such as easy recombination of photogenerated carriers and low visible light utilization, preventing it from reaching its theoretical application value. Therefore, modification is needed to improve its photoelectrocatalytic performance.

[0004] There are reports on cerium-doped bismuth tungstate photocatalytic materials. Generating oxygen vacancies through cerium doping is an effective method to enhance the visible light response of semiconductors. An appropriate amount of oxygen vacancies is not only beneficial to the separation of charge carriers, but also extends the photoresponse of semiconductors to the visible light region. However, the separation efficiency of photogenerated electrons and holes is insufficient and still cannot meet the current requirements of photoelectrocatalysis for material performance. Summary of the Invention

[0005] To address the problems existing in the prior art, this invention provides a cerium-doped bismuth tungstate supported osmium photocatalytic material and its preparation method. The method is convenient to operate, the process is relatively simple, the obtained product has uniform particle size, the synthesis particle size is controllable, there is no pollution, and the cost is low. By supporting osmium, it effectively promotes interfacial charge transfer and provides more active sites, thereby exhibiting significantly improved photoelectrochemical performance.

[0006] This invention is achieved through the following technical solution:

[0007] A method for preparing a bismuth tungstate-supported osmium photocatalytic material doped with cerium includes the following steps:

[0008] S1, bismuth nitrate, sodium tungstate and cerium nitrate are dissolved in deionized water, wherein the molar ratio of bismuth nitrate and cerium nitrate is 5:1, to obtain a mixed solution. The pH of the mixed solution is adjusted to 7-8 to obtain a precursor solution. The precursor solution is kept at 180-210℃ to obtain a reaction solution. The product in the reaction solution is washed, dried and ground to obtain cerium-doped bismuth tungstate.

[0009] S2, bismuth tungstate and osmium powder were uniformly dispersed in deionized water at a mass ratio of 699:(28-143). The deionized water was then evaporated by a water bath. Osmium was loaded onto bismuth tungstate to obtain a composite. The composite was dried and ground to obtain bismuth tungstate-supported osmium photocatalytic material.

[0010] Preferably, the mass ratio of bismuth nitrate, sodium tungstate, and cerium nitrate in S1 is 4.851:1.649:0.434.

[0011] Preferably, in step S1, bismuth nitrate is first added to deionized water at a ratio of 4.851 g: 70 ml, and then magnetically stirred at room temperature until dissolved. Sodium tungstate is then added and stirred until dissolved, and finally cerium nitrate is added and stirred until dissolved to obtain a mixed solution.

[0012] Preferably, in S1, a 2 mol / L NaOH solution is used to adjust the pH of the mixed solution to 7-8.

[0013] Preferably, in step S1, the precursor solution is kept at 180–210°C for 16–20 h to obtain the reaction solution.

[0014] Preferably, in step S1, the precursor solution is heated from room temperature to 180-210°C at a rate of 4-8°C / min, and after holding at this temperature, it is cooled down to 30-50°C at a rate of 3-6°C / min, and then naturally cooled to room temperature before washing the product in the reaction solution.

[0015] Preferably, S1 is washed with deionized water and anhydrous ethanol by centrifugation 3 to 5 times, then vacuum dried at 60 to 80°C for 12 hours, and then ground to obtain the product.

[0016] Preferably, in step S2, bismuth tungstate doped with cerium is first dissolved in deionized water at a ratio of 0.699 g to 60 ml. After ultrasonic dispersion, osmium powder is added and the mixture is stirred in a sealed environment for 5 to 7 hours. Finally, the deionized water is evaporated by a water bath.

[0017] Preferably, the temperature of the water bath in S2 is 70-80°C to obtain the composite. The composite is then dried at 60-70°C for 10-14 hours and ground to obtain a cerium-doped bismuth tungstate supported osmium photocatalyst material.

[0018] A bismuth tungstate photocatalyst supported on osmium, obtained by the preparation method of the bismuth tungstate supported on osmium as described in any one of the above methods.

[0019] Compared with the prior art, the present invention has the following beneficial technical effects:

[0020] This invention discloses a method for preparing osmium photocatalyst material supported on cerium-doped bismuth tungstate. The method involves introducing and regulating crystal defects by doping Bi₂WO₆ with the rare earth element Ce (Ce partially replaces Bi), thereby generating oxygen vacancies to enhance the visible light response of the semiconductor. Appropriate amounts of oxygen vacancies not only facilitate carrier separation but also extend the semiconductor's photoresponse into the visible light region. The osmium is uniformly dispersed with osmium powder in deionized water, and the deionized water is evaporated using a water bath. This allows osmium to be loaded onto the cerium-doped bismuth tungstate. Finally, after drying and grinding, the cerium-doped bismuth tungstate-supported osmium photocatalyst material is obtained. This invention uses a water bath heating method to load metal Os. Because Os has a smaller work function than bismuth tungstate, loading it onto cerium-doped bismuth tungstate creates an ohmic contact. The band bending caused by the ohmic contact prevents charge carrier migration from Os to the cerium-doped bismuth tungstate. Simultaneously, there is no barrier for electrons to enter the metal from the semiconductor, which promotes the migration of photogenerated charge carriers. Incorporating the effects of the built-in electric field and ohmic contact, the transfer rate of photogenerated electrons from Os to cerium-doped bismuth tungstate is extremely fast, approaching zero resistance migration. This directly and effectively improves carrier separation efficiency, thereby achieving higher photocatalytic performance. This invention designs an osmium-supported cerium-doped bismuth tungstate photocatalytic material based on the principles of greenness, simplicity, and efficiency. It is easy to operate, has a relatively simple process, and yields products with uniform particle size.

[0021] The cerium-doped bismuth tungstate-supported osmium photocatalytic material of the present invention utilizes cerium doping to introduce defects into the bismuth tungstate, generating oxygen vacancies that improve the visible light absorption range and charge dynamics within the material, thereby enhancing catalytic activity. The osmium support creates an ohmic contact, eliminating the barrier for electrons to enter the metal from the semiconductor. This facilitates the migration of photogenerated charge carriers, significantly enhancing photocatalytic performance. Attached Figure Description

[0022] Figure 1The images show the XRD patterns of the samples prepared in Examples 1-3 and Comparative Examples 1-2 of this invention.

[0023] Figure 2 This is a SEM image of the comparative example 1Bi2WO6 sample at 1 μm.

[0024] Figure 3 This is a SEM image of the cerium-doped Bi2WO6 sample (Comparative Example 2) at 1 μm.

[0025] Figure 4a This is a SEM image of the sample prepared in Example 1 of the present invention at 5 μm.

[0026] Figure 4b This is a SEM image of the sample prepared in Example 1 of the present invention at 1 μm.

[0027] Figure 5a This is a SEM image of the sample prepared in Example 2 of the present invention at 2 μm.

[0028] Figure 5b This is a SEM image of the sample prepared in Example 2 of the present invention at 1 μm.

[0029] Figure 6a This is a SEM image of the sample prepared in Example 3 of the present invention at 5 μm.

[0030] Figure 6b This is a SEM image of the sample prepared in Example 3 of the present invention at 1 μm.

[0031] Figure 7 The LSV diagrams are of the samples prepared in Example 2 and Comparative Examples 1-2 of this invention. Detailed Implementation

[0032] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.

[0033] This invention discloses a method for preparing osmium photocatalyst material supported on cerium-doped bismuth tungstate, comprising the following steps:

[0034] Step 1: Weigh out a certain amount of Bi(NO3)3·5H2O, Na2WO4·2H2O and Ce(NO3)3·6H2O respectively according to the mass ratio of 4.851:1.649:0.434. All of them are analytical grade (AR) with a purity greater than 99.7%.

[0035] Step 2: Add 4.851g Bi(NO3)3·5H2O to deionized water. To strictly control the filling ratio of the subsequent reaction, use 70ml of deionized water as the dissolution system. Stir magnetically at room temperature until uniform. Then add 1.649g Na2WO4·2H2O and stir until completely dissolved. Add 0.434g Ce(NO3)3·6H2O to the above mixed solution and stir until completely dissolved to obtain the reaction precursor solution. At this time, the molar ratio of Ce(NO3)3·6H2O to Bi(NO3)3·5H2O is 1:5.

[0036] Step 3: Adjust the pH of the precursor solution to 7-8 using a 2 mol / L NaOH solution;

[0037] Step 4: Transfer the pH-adjusted reaction precursor solution into a polytetrafluoroethylene reactor for hydrothermal reaction. Set the temperature to 180–210℃ and the time to 16–20 h. The hydrothermal reaction temperature is increased from room temperature to the reaction temperature at a rate of 4–8℃ / min. After the reaction, the temperature is reduced to 30–50℃ at a rate of 3–6℃ / min and then allowed to cool naturally to room temperature.

[0038] Step 5: After cooling to room temperature, the product is taken out and washed by centrifugation with deionized water and anhydrous ethanol 3 to 5 times respectively. Then it is vacuum dried at 60 to 80°C for 12 hours and then ground to obtain a cerium-doped bismuth tungstate (BCeWO) photocatalytic material.

[0039] Step 6: Weigh 0.669g of BCEWO material and dissolve it in 60ml of deionized water. After ultrasonic dispersion, add a certain amount of osmium powder and place it on a magnetic stirrer to stir for 5-7 hours to ensure thorough mixing. Cover the mouth of the beaker with plastic wrap to prevent impurities from contaminating the product, so that Os is loaded on the cerium-doped bismuth tungstate material.

[0040] Specifically, three portions of 0.699 g (1.5 mmol) of BCaWO material were weighed and added to 60 ml of deionized water respectively, and dispersed by sonication. Osmium powder of 0.028 g (0.15 mmol), 0.057 g (0.3 mmol), and 0.143 g (0.75 mmol) were weighed and added to the uniformly dispersed BCaWO solution respectively; at this point, the Os loading was 10%, 20%, and 50%.

[0041] Step 7: Dry the mixture obtained in Step 6 using a constant temperature water bath. Set the water bath drying temperature to 70-80℃ to dry the Os-loaded bismuth tungstate material until all moisture evaporates. Cover the mouth of the beaker with plastic wrap to prevent impurities from contaminating the product. Then place it in a drying oven to dry at a temperature of 60-70℃ for 10-14 hours. After drying, take out the material and grind it to obtain the bismuth tungstate-loaded Os photocatalytic material.

[0042] The photoelectrocatalytic water splitting performance is typically measured using a three-electrode system on an electrochemical workstation. In this invention, a CHI670E electrochemical workstation was used to measure the photoelectrocatalytic properties of the prepared samples in a 1M KOH solution (electrolyte, pH = 13). During the test, the working electrode, reference electrode, and counter electrode were the photocathode, Ag / AgCl (or saturated calomel electrode SCE), and platinum sheet, respectively, all placed together in the electrolyte. The LSV curve was obtained by scanning at a rate of 10 mV / s for -0.8–1.3 V vs. RHE.

[0043] The present invention will be further described in detail below through specific embodiments.

[0044] Example 1

[0045] A method for preparing a bismuth tungstate-supported osmium photocatalytic material doped with cerium includes the following steps:

[0046] Step 1: Weigh out 4.851g of Bi(NO3)3·5H2O, 1.649g of Na2WO4·2H2O and 0.434g of Ce(NO3)3·6H2O raw materials, all of which are analytical grade (AR).

[0047] Step 2: Add 4.851g of Bi(NO3)3·5H2O to deionized water. In order to strictly control the reaction filling ratio, use 70ml of deionized water as the dissolution system. Stir magnetically at room temperature. After stirring evenly, add 1.649g of Na2WO4·2H2O and stir until completely dissolved. Finally, add 0.434g of Ce(NO3)3·6H2O to the above mixed solution and stir until completely dissolved to obtain the reaction precursor solution.

[0048] Step 3: Adjust the pH of the precursor solution to 7 using a 2 mol / L NaOH solution;

[0049] Step 4: The pH-adjusted reaction precursor solution is transferred into a polytetrafluoroethylene reactor for hydrothermal reaction at a temperature of 200°C for 18 hours.

[0050] The hydrothermal reaction temperature was increased from room temperature to the reaction temperature at a rate of 5℃ / min, and after the reaction, the temperature was reduced to 40℃ at a rate of 5℃ / min, and then naturally cooled to room temperature.

[0051] Step 5: After the hydrothermal reaction is completed, the product is removed and washed three times by centrifugation with deionized water and anhydrous ethanol, respectively. It is then vacuum dried at 70°C for 12 hours and ground to obtain a cerium-doped bismuth tungstate (BCeWO) photoelectrocatalytic material.

[0052] Step 6: Weigh 0.669g of BCEWO material and dissolve it in 60ml of deionized water. After ultrasonic dispersion, add 0.028g of osmium powder and place it on a magnetic stirrer to stir for 6 hours to ensure thorough mixing. Cover the mouth of the beaker with plastic wrap to prevent impurities from contaminating the product, so that Os is loaded on the cerium-doped bismuth tungstate material.

[0053] Step 7: Dry the mixture obtained in Step 6 using a constant temperature water bath. Set the water bath drying temperature to 80℃ to dry the Os-loaded bismuth tungstate material until all the moisture evaporates. Cover the mouth of the beaker with plastic wrap to prevent impurities from contaminating the product. Then place it in a drying oven to dry at 70℃ for 12 hours. After drying, take out the material and grind it to obtain the bismuth tungstate-loaded Os photoelectrocatalytic material.

[0054] Example 2:

[0055] A method for preparing a bismuth tungstate-supported osmium photocatalytic material doped with cerium includes the following steps:

[0056] Step 1: Weigh out 4.851g of raw material Bi(NO3)3·5H2O, 1.649g of Na2WO4·2H2O and 0.434g of Ce(NO3)3·6H2O respectively, all of which are analytical grade (AR);

[0057] Step 2: Add 4.851g of Bi(NO3)3·5H2O to deionized water. In order to strictly control the reaction filling ratio, use 70ml of deionized water as the dissolution system. Stir magnetically at room temperature. After stirring evenly, add 1.649g of Na2WO4·2H2O and stir until completely dissolved. Finally, add 0.434g of Ce(NO3)3·6H2O to the above mixed solution and stir until completely dissolved to obtain the reaction precursor solution.

[0058] Step 3: Adjust the pH of the precursor solution to 7 using a 2 mol / L NaOH solution;

[0059] Step 4: The pH-adjusted reaction precursor solution is transferred into a polytetrafluoroethylene reactor for hydrothermal reaction at a temperature of 200°C for 18 hours.

[0060] The hydrothermal reaction temperature was increased from room temperature to the reaction temperature at a rate of 5℃ / min, and after the reaction, the temperature was reduced to 40℃ at a rate of 5℃ / min, and then naturally cooled to room temperature.

[0061] Step 5: After the hydrothermal reaction is completed, the product is removed and washed three times by centrifugation with deionized water and anhydrous ethanol, respectively. It is then vacuum dried at 70°C for 12 hours and ground to obtain a cerium-doped bismuth tungstate (BCeWO) photoelectrocatalytic material.

[0062] Step 6: Weigh 0.669g of BCEWO material and dissolve it in 60ml of deionized water. After ultrasonic dispersion, add 0.057g of osmium powder and place it on a magnetic stirrer to stir for 6 hours to ensure thorough mixing. Cover the mouth of the beaker with plastic wrap to prevent impurities from contaminating the product, so that Os is loaded on the cerium-doped bismuth tungstate material.

[0063] Step 7: Dry the mixture obtained in Step 6 using a constant temperature water bath. Set the water bath drying temperature to 80℃ to dry the Os-loaded bismuth tungstate material until all the moisture evaporates. Cover the mouth of the beaker with plastic wrap to prevent impurities from contaminating the product. Then place it in a drying oven to dry at 70℃ for 12 hours. After drying, take out the material and grind it to obtain the bismuth tungstate-loaded Os photoelectrocatalytic material.

[0064] Example 3:

[0065] A method for preparing a bismuth tungstate-supported osmium photocatalytic material doped with cerium includes the following steps:

[0066] Step 1: Weigh out 4.851g of raw material Bi(NO3)3·5H2O, 1.649g of Na2WO4·2H2O and 0.434g of Ce(NO3)3·6H2O respectively, all of which are analytical grade (AR);

[0067] Step 2: Add 4.851g of Bi(NO3)3·5H2O to deionized water. In order to strictly control the reaction filling ratio, use 70ml of deionized water as the dissolution system. Stir magnetically at room temperature. After stirring evenly, add 1.649g of Na2WO4·2H2O and stir until completely dissolved. Finally, add 0.434g of Ce(NO3)3·6H2O to the above mixed solution and stir until completely dissolved to obtain the reaction precursor solution.

[0068] Step 3: Adjust the pH of the precursor solution to 7 using a 2 mol / L NaOH solution;

[0069] Step 4: The pH-adjusted precursor solution is transferred into a polytetrafluoroethylene reactor for hydrothermal reaction at a temperature of 200°C for 18 hours. The hydrothermal reaction temperature is increased from room temperature to the reaction temperature at a rate of 5°C / min, and then decreased to 40°C at a rate of 5°C / min after the reaction, and then allowed to cool naturally to room temperature.

[0070] Step 5: After the hydrothermal reaction is completed, the product is removed and washed three times by centrifugation with deionized water and anhydrous ethanol, respectively. It is then vacuum dried at 70°C for 3 hours and ground to obtain a cerium-doped bismuth tungstate (BCeWO) photocatalytic material.

[0071] Step 6: Weigh 0.669g of BCEWO material and dissolve it in 60ml of deionized water. After ultrasonic dispersion, add 0.143g of osmium powder and place it on a magnetic stirrer to stir for 6 hours to ensure thorough mixing. Cover the mouth of the beaker with plastic wrap to prevent impurities from contaminating the product, so that Os is loaded on the cerium-doped bismuth tungstate material.

[0072] Step 7: Dry the mixture obtained in Step 6 using a constant temperature water bath. Set the water bath drying temperature to 80℃ to dry the Os-loaded bismuth tungstate material until all the moisture evaporates. Cover the mouth of the beaker with plastic wrap to prevent impurities from contaminating the product. Then place it in a drying oven to dry at 70℃ for 12 hours. After drying, take out the material and grind it to obtain the bismuth tungstate-loaded Os photoelectrocatalytic material.

[0073] Comparative Example 1:

[0074] A method for preparing a bismuth tungstate photoelectrocatalytic material includes the following steps:

[0075] Step 1: Weigh 3.123g of Bi(NO3)3·5H2O and 1.062g of Na2WO4·2H2O raw materials, both of which are analytical grade (AR);

[0076] Step 2: Add 3.123g of Bi(NO3)3·5H2O to deionized water. In order to strictly control the reaction filling ratio, 70ml of deionized water is used as the dissolution system. Stir magnetically at room temperature. After stirring evenly, add 1.062g of Na2WO4·2H2O and stir until completely dissolved to obtain the reaction precursor solution.

[0077] Step 3: Adjust the pH of the precursor solution to 7 using a 2 mol / L NaOH solution;

[0078] Step 4: The pH-adjusted precursor solution is transferred into a polytetrafluoroethylene reactor for hydrothermal reaction at a temperature of 200°C for 18 hours. The hydrothermal reaction temperature is increased from room temperature to the reaction temperature at a rate of 5°C / min, and then decreased to 40°C at a rate of 5°C / min after the reaction, and then allowed to cool naturally to room temperature.

[0079] Step 5: After the hydrothermal reaction is completed, the product is removed and washed three times by centrifugation with deionized water and anhydrous ethanol, respectively. It is then vacuum dried at 70°C for 12 hours and ground to obtain a bismuth tungstate photocatalytic material.

[0080] Comparative Example 2:

[0081] A method for preparing a cerium-doped bismuth tungstate photocatalytic material includes the following steps:

[0082] Step 1: Weigh out 4.851g of raw material Bi(NO3)3·5H2O, 1.649g of Na2WO4·2H2O and 0.434g of Ce(NO3)3·6H2O respectively, all of which are analytical grade (AR);

[0083] Step 2: Add 4.851g of Bi(NO3)3·5H2O to deionized water. In order to strictly control the reaction filling ratio, use 70ml of deionized water as the dissolution system. Stir magnetically at room temperature. After stirring evenly, add 1.649g of Na2WO4·2H2O and stir until completely dissolved. Finally, add 0.434g of Ce(NO3)3·6H2O to the above mixed solution and stir until completely dissolved to obtain the reaction precursor solution.

[0084] Step 3: Adjust the pH of the precursor solution to 7 using a 2 mol / L NaOH solution;

[0085] Step 4: The pH-adjusted precursor solution is transferred into a polytetrafluoroethylene reactor for hydrothermal reaction at a temperature of 200°C for 18 hours. The hydrothermal reaction temperature is increased from room temperature to the reaction temperature at a rate of 5°C / min, and then decreased to 40°C at a rate of 5°C / min after the reaction, and then allowed to cool naturally to room temperature.

[0086] Step 5: After the hydrothermal reaction is completed, the product is removed and washed three times by centrifugation with deionized water and anhydrous ethanol, respectively. It is then vacuum dried at 70°C for 12 hours and ground to obtain a cerium-doped bismuth tungstate (BCeWO) photoelectrocatalytic material.

[0087] Figure 1 XRD patterns of cerium-doped Bi₂WO₆ samples loaded with different amounts of Os, cerium-doped Bi₂WO₆ samples, and pure Bi₂WO₆ samples are shown. It can be seen that the diffraction peaks of the cerium-doped bismuth tungstate sample are in perfect agreement with the standard card (PDF#26-1044) for orthorhombic Bi₂WO₆. The diffraction peaks of BCaWO₆ are similar to those of pure Bi₂WO₆, indicating that Ce doping did not change the crystal structure of Bi₂WO₆, but rather directly incorporated it into the crystal phase. The diffraction peaks of the doped material show a slight rightward shift at 32.76° compared to pure Bi₂WO₆, which is due to the Ce doping... 3+ The radius is smaller than Bi 3+ radius, Ce 3+ It was doped into the BWO lattice, replacing part of the Bi. 3+This caused crystal distortion in bismuth tungstate. No Ce diffraction peaks were observed in any of the samples, likely due to the low content of Ce introduced. After loading Os, some impurity peaks appeared, which perfectly matched the standard card (PDF#06-0622) for hexagonal Os. Furthermore, the diffraction peak intensity gradually increased with increasing Os loading content, indicating that the samples contained both orthorhombic Bi₂WO₆ and hexagonal Os crystal forms.

[0088] Figure 2 , Figure 3 , Figure 4a , Figure 4b , Figure 5a , Figure 5b , Figure 6a , Figure 6b SEM images of pure bismuth tungstate (Comparative Example 1), cerium-doped Bi2WO6 sample (Comparative Example 2), and cerium-doped Bi2WO6 samples with different amounts of Os (10-50%) (Examples 1-3). Figure 2 The image shows a scanned image of a pure-phase bismuth tungstate sample (Comparative Example 1). Figure 3 The image shows a scanned image of a cerium-doped Bi₂WO₆ sample (Comparative Example 2). Figure 4a , Figure 4b Scanned images of a BCaWO3 sample loaded with 10% Os (Example 1). Figure 5a , Figure 5b Scanned images of a BCaWO3 sample loaded with 30% Os (Example 2). Figure 6a , Figure 6b Scanned images of a BCaWO3 sample loaded with 50% Os (Example 3). And from... Figure 2 It can be seen that pure phase bismuth tungstate is composed of irregularly stacked two-dimensional nanosheets with a thickness of 30-50 nm (Comparative Example 1). Figure 3 After Ce was doped, the nanosheets became significantly thinner and stacked together to form a layered structure (Comparative Example 2).

[0089] Figure 4a , Figure 4b In Example 1, compared to BCaWO, the morphology did not change significantly after loading 10% Os, but some small particles were observed to be attached to the nanosheets. Figure 5a , Figure 5b In Example 2, after loading 20% ​​Os, the number of small particles attached to the nanosheets increased. Figure 6a , Figure 6b In Example 3, after loading 50% Os, the nanosheets agglomerated.

[0090] Figure 7The photoelectrocatalytic test results of the product samples from Example 2, Comparative Example 1, and Comparative Example 2 show that the material loaded with 20% Os exhibits the best photoelectrocatalytic performance, with a current density significantly superior to that of cerium-doped bismuth tungstate and pure-phase bismuth tungstate. This is mainly due to the synergistic effect of the small amount of bulk Os and the two-dimensional layered BCaWO in Example 2 (Figure 5), which effectively promotes electron-hole separation and inhibits their recombination in the photoelectrocatalytic reaction, thereby greatly enhancing the photoelectrocatalytic performance.

[0091] The above descriptions are merely some embodiments of the present invention, not all embodiments. Any equivalent modifications made by those skilled in the art to the technical solutions of the present invention based on the above embodiments are embodiments covered by the specific embodiments of the present invention.

Claims

1. A method for preparing a cerium-doped bismuth tungstate-supported osmium photocatalytic material, characterized in that, Includes the following steps: S1. First, bismuth nitrate was added to deionized water at a ratio of 4.851 g: 70 ml. After dissolving by magnetic stirring at room temperature, sodium tungstate was added and stirred until dissolved. Finally, cerium nitrate was added and stirred until dissolved. The mass ratio of bismuth nitrate, sodium tungstate, and cerium nitrate was 4.851: 1.649: 0.434 to obtain a mixed solution. The pH of the mixed solution was adjusted to 7-8 to obtain a precursor solution. The precursor solution was kept at 180-210℃ for 16-20 h to obtain a reaction solution. The product in the reaction solution was washed, dried, and ground to obtain cerium-doped bismuth tungstate. S2, firstly, cerium-doped bismuth tungstate is dissolved in deionized water at a ratio of 0.699 g : 60 ml. After ultrasonic dispersion, osmium powder is added at a mass ratio of 699 : (28~143). The mixture is stirred in a sealed environment for 5~7 h. Finally, the deionized water is evaporated by a water bath at a temperature of 70~80℃. Osmium is loaded onto the cerium-doped bismuth tungstate to obtain a composite. The composite is dried at 60~70℃ for 10~14 h and then ground to obtain the osmium photocatalyst material supported on cerium-doped bismuth tungstate.

2. The method for preparing osmium photocatalyst material supported on cerium-doped bismuth tungstate according to claim 1, characterized in that, In S1, the pH of the mixed solution was adjusted to 7-8 using a 2 mol / L NaOH solution.

3. The method for preparing osmium photocatalyst material supported on cerium-doped bismuth tungstate according to claim 1, characterized in that, S1 heats the precursor solution from room temperature to 180–210°C at a rate of 4–8°C / min. After holding at this temperature, it is cooled to 30–50°C at a rate of 3–6°C / min, and then allowed to cool naturally to room temperature. The product in the reaction solution is then washed.

4. The method for preparing osmium photocatalyst material supported on cerium-doped bismuth tungstate according to claim 1, characterized in that, S1 was washed with deionized water and anhydrous ethanol by centrifugation 3 to 5 times, then vacuum dried at 60 to 80°C for 12 hours, and then ground to obtain the product.

5. An osmium-loaded osmium-loaded osmium-loaded osmium-loaded osmium-loaded osmium photocatalytic material obtained by the preparation method of the osmium-loaded ... photocatalytic material according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Visible-light response Ce doped Bi2WO6 microcrystal, preparation method and application thereof

    CN103611527A

  • Ag / Bi2WO6 photocatalyst and preparation method thereof

    CN108745357A